2011
DOI: 10.1002/pssb.201147033
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of structural, elastic, electronic and optical properties of Nb2N and Ta2N compounds

Abstract: Structural, elastic, electronic and optical properties of hexagonal b-Nb 2 N and b-Ta 2 N compounds are studied for different pressures. The computational technique is based on a plane wave pseudo potential (PWPP) method. The exchange correlation is treated using a generalized gradient approximation (GGA). We evaluate ground state quantities such as lattice parameter, bulk modulus and its pressure derivative, as well as elastic constants. The calculated equilibrium lattice is in rather good agreement with expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Inspired by Ta 2 N 3 compound stabilized at high-pressure, Jiang et al 35 first proposed that U 2 S 3 type Nb 2 N 3 may be stable at wide pressures, and is a potential candidate for hard material. Hexagonal and trigonal structured Nb 2 N materials have also been studied by Chihi et al 37 and Yu et al 38 In addition, much attentions have been focused on the mononitride of Nb since it is proposed that δ-NbN is a superconducting phase with a high transition temperature of 17.8 K. 33 The δ-NbN is a high temperature phase and can be stable at above 1070 -1225 °C. Hexagonal and trigonal structured Nb 2 N materials have also been studied by Chihi et al 37 and Yu et al 38 In addition, much attentions have been focused on the mononitride of Nb since it is proposed that δ-NbN is a superconducting phase with a high transition temperature of 17.8 K. 33 The δ-NbN is a high temperature phase and can be stable at above 1070 -1225 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by Ta 2 N 3 compound stabilized at high-pressure, Jiang et al 35 first proposed that U 2 S 3 type Nb 2 N 3 may be stable at wide pressures, and is a potential candidate for hard material. Hexagonal and trigonal structured Nb 2 N materials have also been studied by Chihi et al 37 and Yu et al 38 In addition, much attentions have been focused on the mononitride of Nb since it is proposed that δ-NbN is a superconducting phase with a high transition temperature of 17.8 K. 33 The δ-NbN is a high temperature phase and can be stable at above 1070 -1225 °C. Hexagonal and trigonal structured Nb 2 N materials have also been studied by Chihi et al 37 and Yu et al 38 In addition, much attentions have been focused on the mononitride of Nb since it is proposed that δ-NbN is a superconducting phase with a high transition temperature of 17.8 K. 33 The δ-NbN is a high temperature phase and can be stable at above 1070 -1225 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Chihi et al 36 investigated the crystal structures and elastic properties of Nb 4 N 5 and Nb 5 N 6 compounds. Hexagonal and trigonal structured Nb 2 N materials have also been studied by Chihi et al 37 and Yu et al 38 In addition, much attention has been focused on the mononitride of Nb since it is proposed that d-NbN is a superconducting phase with a high transition temperature of 17.8 K. 33 d-NbN is a high temperature phase and can be stable at above 1070-1225 1C. First-principles studies showed that the cubic phase is unstable at low temperature, 39,40 and the ground state of NbN is stabilized in the hexagonal CW type structure.…”
Section: Introductionmentioning
confidence: 99%
“…The a-Ta 2 N is an amorphous phase of Ta 2 N. 9 b-Ta 2 N adopts the Fe 2 N-type structure. 10 The TaN exists in three forms: q-TaN (WC-type structure), d-TaN (NaCl-type structure), and 3-TaN (CoSn-type structure). 11,12 The rst principle calculations indicate that the presence of Ta vacancies can reduce the density of state (DOS) around the Fermi level and result in a metal-to-insulator transition in d-TaN.…”
Section: Introductionmentioning
confidence: 99%
“…where C ij are the stiffness coefficients of the β-Nb 2 N (C 11 = 533 GPa, C 12 = 238 GPa, C 13 = 179 GPa, C 33 = 568 GPa). 17) The estimated in-plane tensile biaxial stress of the β-Nb 2 N on 6H-SiC is 0.2 GPa, and its component along c-direction is zero. Thus, the film is partially strained.…”
mentioning
confidence: 96%